2019
DOI: 10.1155/2019/2061868
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor 2 (CXCR2) Gene Variants and Their Association with Periodontal Bacteria in Patients with Chronic Periodontitis

Abstract: Periodontitis, an inflammatory disease caused by subgingival Gram-negative (G-) bacteria, is linked with loss of the connective tissue and destruction of the alveolar bone. In the regulation of inflammatory response, chemokine receptor 2 (CXCR2), a specific receptor for interleukin-8 and neutrophil chemoattractant, plays an important role. The first aim of this study was to investigate the CXCR2 gene variability in chronic periodontitis (CP) patients and healthy nonperiodontitis controls in the Czech populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
“…Kavrikova et al analyzed the association of CXCR2 gene variants with periodontal bacteria in patients with chronic periodontitis in the Czech population and found that the C allele of rs2230054 and the T allele of rs1126579 in men were closely associated with Aggregatibacter actinomycetemcomitans, the main etiological agent of periodontitis. 15 In the Brazilian population, among three SNPs of the CXCR2 gene, including rs2230054, rs1126579, and rs1126580, only rs1126580 showed significant association with periodontitis of patients. 26…”
Section: Discussionmentioning
confidence: 94%
“…14 Kavrikova et al have reported that CXCR2 gene variants are correlated with the subgingival Grannegative bacteria in chronic periodontitis patients, which is the major cause of periodontitis. 15 Therefore, CXCR2 was speculated to be involved in the pathogenesis of periimplantitis.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, haplogenotypes (combinations of unphased genotypes) have been used in association studies [ 55 ]. Here, a simple online application for the calculation of haplogenotypes by combining determined genotypes of two to ten SNPs has been prepared to facilitate further statistical analyses.…”
Section: Discussionmentioning
confidence: 99%